Isolation of Scardovia wiggsiae using real-time polymerase chain reaction from the saliva of children with early childhood caries - Preetika Chandna; Nikhil Srivastava; Alpana Sharma; Vrinda Sharma; Nidhi Gupta; Vivek Kumar Adlakha (Wolters Kluwer Medknow Publications, 2018)
Aim: This study aimed to quantitatively assess the levels of Scardovia wiggsiae in caries-free and early childhood caries (ECC)- and severe ECC (SECC)-affected children using real-time polymerase chain reaction (RT-PCR). Methods: Forty-five children aged <71 months were randomly recruited from the Outpatient Clinic at the Department of Pedodontics and Preventive Dentistry at Subharti Dental College and Hospital, Meerut, India. Fifteen children suffering from ECC, 15 with SECC, and 15 children without ECC were enrolled in the study. About 1-2 mL of unstimulated saliva was collected and subjected to microbial analysis using RT-PCR. Results: The SECC group (n = 15) was found to have significantly higher mean relative 16s rRNA expression of S. wiggsiae (3.67) than both ECC (n = 15) and controls (n = 15) (1.69 and 0.85, respectively). S. wiggsiae was detected in 86.7% of the SECC and 60% ECC group and was detected negligibly in the control (caries free) group. The correlation of decayed, missing, or filled surface levels with 16s rRNA levels showed significant positive correlation with 16S rRNA in both ECC and SECC patients. Conclusion: Salivary levels of S. wiggsiae were significantly associated with ECC in children. S. wiggsiae represents a new frontier in the microbial etiology of ECC. This may lead to the development of new antimicrobial agents targeted to this organism and improve the treatment of ECC.